Crossing boundaries: religion, sexuality and identity in the lives of Zanele Muholi and Nkunzi Zandile Nkabinde - Carlse, Janine (Department of Religious Studies, 2015)
The 21st century has brought new concerns to the fore within South Africa's democracy. Sexuality and the freedom to express one's sexual identity are currently at the forefront of academic writing and investigation in the social sciences in Africa. In following this interdisciplinary line of research, this thesis explores some of the ways that religious ideologies influence women's agency in relation to their sexuality and identity. In particular, I examine how dominant religious and cultural norms framed by patriarchal and heteronormative ideals are negotiated by black lesbian Zulu women. My research is focused on the lives of two Zulu women, lesbian activist photographer Zanele Muholi and lesbian sangoma Nkunzi Zandile Nkabinde, who inhabit very different social realities from one another. Both these women are redefining the paths of women's sexuality in their specific contexts, while taking somewhat different approaches to this task. I argue that religion has a very powerful impact on the way that these women approach their sexuality and sexual choices, whether directly or indirectly, with a hybridity of Zulu tradition and Christianity influencing their lives in various ways. Muholi and Nkabinde are directly affected by religious ideologies through the way that they have to reconcile their sexuality with their religion and culture; and indirectly through the way that certain heteronormative religious ideologies have influenced the political and social structures within South Africa. Religious ideologies that divide humanity into the essentialist complimentary categories of masculine and feminine pose a problem for people who straddle both these spheres. By not fitting neatly into any of these categories, black lesbians are often viewed or depicted as not fitting into the social structure, particularly within and around urban townships, giving reason for their oppression and marginalisation.